Ian Keable. Charles Dickens Magician: Conjuring in Life, Letters and Literature. Iankeable.co.uk, 2014. Pp. xviii+268. - Rouse C., Andrew (FOCUS: Papers in English Literary and Cultural Studies, 2016)
As Ian Keable may not be entirely familiar to literary scholars, some introduction may be necessary. Keable is a professional magician, Member of the Inner Magic Circle, and winner of the Magic Circle Comedy Award. He has published several books and been a presenter on BBC Radio 4 and is an accredited lecturer for the British Arts Society, specializing in Dickensian conjuring and eighteenth-century hoaxes. He writes a meticulous regular and informative monthly blog.